How do wage earners respond to a large kink? Evidence on earnings and deduction behavior from Austria - Jörg Paetzold (University of Salzburg, Department of Social Sciences and Economics, 2017)
This paper contributes to recent literature emphasizing the importance to identify the different channels along which taxable income responses occur. Using bunching techniques and exploiting a large first kink point where marginal tax rates increase by as much as 38 percentage points, we recover modest gross wage earnings responses of Austrian employees. Next, we show that when accounting for deduction behavior, the additional mass of wage earners at the kink increases by around 50%. We find direct evidence for wage earners targeting the kink with their deduction claiming. Finally, we use a novel estimation strategy to show evidence that the probability of claiming a deduction depends on its (net-of-tax) cash value, and we provide a new estimate for the deduction elasticity. In sum, our results suggest that distinguishing between earnings and deduction responses matters even for taxpayers with only limited possibilities to shelter taxable income.
Keywords: H21; H24; J22; 330; Bunching; elasticity of wage earnings and deductions; tax expenditures; deduction behavior; administrative data